VOLUME 5, NO 1 (2017) - Chief, Editor In (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Dear readers, you are holding the eighth issue (Vol V, No 1) of Aro the Scientific Journal of Koya University in your hand. Aro is publishing its 3rd issue as an internationally listed Scientific Journal in Kurdistan Region/Iraq. Notably, Aro has been accepted for indexing in the Emerging Sources Citation Index (ESCI), a new edition of Web of Science™ as of Feb 2016. Content in this index is under consideration by Thomson Reuters to be accepted in the Science Citation Index Expanded™ (SCIE). Aro’s individual articles are currently listed by Thomson Reuters using articles unique DOI numbers which is a historical achievement for our academic community. Aro is starting its fifth year journey in leading the quality of regional scientific publications with global impact. The editorial team is determined to keep the path of such a mission and sustain Aro’s future publications with reliable quality in mind. Despite the ongoing regional economic downturn and war on terror which have had a great impact on scientific research activities and funding of the regional universities in general and Koya University in particular, Aro is continuing to receive great numbers of well motivated quality papers which shows its steadily growing trust among researchers in the region, demanding the increased volume of publication. Nevertheless, Aro is finding more focus in applied sciences with research values in current regional issues having International impacts. Aro was created with a long-term visions of becoming accessible to all researchers in Kurdistan and beyond, and covering a wide range of scholarly disciplines in sciences. Aro aspires to become a channel for exchanging of scholarly research by establishing academic connections between scholars globally. Therefore, we are asking our wider academic community to join us in this endeavor. Aro is a journal of original scientific research, global news, review paper, letters and commentary. The Aro Scientific Journal is a peer-reviewed, open access journal that publishes original research articles as well as review articles in areas of natural sciences and technology. In this issue you will have access to original research papers in variety of areas, such as Petroleum, Physics, Chemical Engineering, Biochemistry, Engineering and Materials Science. The warm responses from researchers, academics and professionals in the last four years have made us create a wider Editorial Board which serves the wider submitted scientific manuscripts. However, it is clear that having a dedicated and well-organized editorial board for the journal is only one side of the coin. The other is the ability to attract submissions of quality research and scholarly work. We are thankful to all of those who put their trust in Aro and presented their original research work for publication in Vol V, No 1 of the journal, as well as, our thanks are extended to the 12 peer-reviewers from the Universities worldwide for their efforts in reviewing and enabling this issue of Aro. Your support and feedback are invited and appreciated. Dilan M. Rostam Editor-in-Chief Wali M Hamad Executive Publisher Dilan M. Rostam, Salah I. Yahya, Shwan K. Rachid, Basim M.Fadhil, Fahmi F. Muhammad and Mohammed H. S. Zangana Executive Editorial Board